META ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KETRAMPILAN BERPIKIR KRITIS SISWA SD - Risma Ayu Kusumaningrum; Firosalia Kristin (STKIP ROKANIA, 2021)
This study aims to analyze the Problem Based Learning learning model in improving critical thinking skills of elementary school students. This type of research is a meta-analysis. The objects in this research are journal articles, academic works, and other scientific works obtained through Google Scholar, Google Scholar about the Problem Based Learning learning model in improving critical thinking skills of elementary school students. This data analysis technique uses a quantitative comparison model to find out how much the Problem Based Learning learning model can improve the critical thinking skills of elementary school students. Based on the results of the analysis of the use of the Problem Based Learning learning model in learning, it is proven that it can improve students' critical thinking skills with the lowest score percentage of 3.96% and the highest score of 54% with an overall average of 21.20%. From the results of the analysis, it can be concluded that the Problem Based Learning learning model affects students' critical thinking skills.